Nodal involvement in Oral Squamous Cell Carcinoma (SCC) patients with and without Oral Sub Mucous Fibrosis (OSMF): A Comparative Study - Gaurav Singh; Amar Singh Rana; Anshuman Kumar; Ashish Prajapati; Shubham Kumar; Parul Singh (Journal of Oral Biology and Craniofacial Research)
Aim: The aim of the study is to compare and evaluate neck node status of oral cancer patients with and without Oral Sub Mucous Fibrosis (OSMF) treated surgically. Methodology: A total of 50 patients of Indian origin who were diagnosed with Squamous Cell Carcinoma (SCC) of oral cavity and had not taken any prior treatment were included in the study. Clinical examination and metastatic workup was done for all patients. Patients diagnosed with resectable primary and without distant metastasis were taken up for surgery. For all patients, resected specimens were sent for radical histopathological examination. Result: The differences in nodal involvement in T1, T2 & T3 sized lesions were non-significant, while in T4 sized lesions, a statistically significant lower incidence of nodal involvement in patients with-OSMF as compared to patients without OSMF was observed. Conclusion: Presence of N0 neck in T4 lesions in oral SCC patients with OSMF has potential implications on the present pattern of spread and treatment protocols, leading to need for further research with OSMF as independent risk factor for nodal involvement